1974
DOI: 10.1071/sr9740147
|View full text |Cite
|
Sign up to set email alerts
|

Studies on potassium. IV. Interspecific differences in the uptake of non-exchangeable potassium

Abstract: Five soils were cropped with four plant species in pot experiments in the glasshouse, without addition of potassium, until growth virtually ceased, after which the depleted soils were replanted with either the same species, or a different one, to test the reproducibility of the 'exhaustion' conditions imposed. Uptake of potassium by the plants exceeded the changes in exchangeable potassium in four soils; the excess amounts taken up differed markedly between species and these differences were reproducible on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…When assessed by plant K uptake, it can be termed as "K-supplying capacity" whereas if assessed by extracting the soil with one or more extractions, a chemical index of available K (K-releasing capacity), can be the true index of plant available K. Consequently, many investigators reported, while "plant available K" can be equated to the K-supplying capacity of the soil, it can only be related to the K-releasing capacity. Thus, both K-releasing and K-supplying capacity can be considered the measures of the ability of a soil to supply K to plants [50][51][52]. The amount of total K uptake by plants from a soil depends on the potential of K-supplying capacity.…”
Section: Discussionmentioning
confidence: 99%
“…When assessed by plant K uptake, it can be termed as "K-supplying capacity" whereas if assessed by extracting the soil with one or more extractions, a chemical index of available K (K-releasing capacity), can be the true index of plant available K. Consequently, many investigators reported, while "plant available K" can be equated to the K-supplying capacity of the soil, it can only be related to the K-releasing capacity. Thus, both K-releasing and K-supplying capacity can be considered the measures of the ability of a soil to supply K to plants [50][51][52]. The amount of total K uptake by plants from a soil depends on the potential of K-supplying capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Fergus & Martin (1974) discussed some of the evidence for differences among plant species in their ability to absorb initially nonexchangeable K, and also presented the results of a pot trial showing such differences among four plant species, including lucerne. They postulated that these differences may be related to the degree of tolerance shown by the plant to low K concentrations in the soil solution.…”
Section: Received 1 November 1976mentioning
confidence: 99%
“…However, non-exchangeable K is often significant for crops: experience shows that it is taken up concurrently with exchangeable K (Russell, 1973). In pot experiments concurrent release has been shown by Sinclair (1979) although not by Fergus & Martin (1974). Kaufman & Bouldin (1967) measured diffusion of K to H-resin and demonstrated that slow release of non-exchangeable K occurred alongside the diffusion of exchangeable K: uptake by onion roots can (greatly) exceed that predicted from resin measurements (Bagshaw et al, 1968;Dunham & Nye, 1976).…”
Section: Introductionmentioning
confidence: 95%